How responsive is Nigeria’s cassava seedsystem to farmers’ demand? Exploring supplyand demand interactions in three farmingcommunities - Pircher, T.; Stuart, E.R.; Almekinders, Conny J.M.; Obisesan, D.; Nitturkar, H.; Asumugha, G.; Azaino, E.; Knierim, A. (Informa UK Limited, 2022)
Based on a concept for demand-orientation in seed systems, we characterized Nigeria’s cassava (Manihot esculenta) seed system from national to local level and farmers’ demand in three study sites. Interviews with seed-system actors explained their roles for supply-side functions. Focus group discussions and a survey described multiple aspects of farmers’ demand. Our findings show that the national agriculture development program alone did not have the capacity to supply farmers with sufficient seed of desired varieties. Seed exchange between farmers and informal seed sellers contributed to the distribution of seed and new varieties. The presence of seed sellers and farmers’ demand for cassava seed varied between the three study sites, farmer types and gender. We conclude that informal seed sellers and village seed entrepreneurs have a potential to respond to farmers’ heterogeneous demands. However, without recurrent demand for specialized seed pro-duction or continuous support from the formal system, they do not reach underserved markets.